Simultaneous Saccharification and Fermentation of Oil Palm Empty Fruit Bunch Fiber Kraft Pulp to Produce Ethanol - Yanni Sudiyani; lrni Fitria; Tami Idiyanti; Wawan K. Haroen; Euis Hermiati (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
The effects of substrate concentration on ethanol production from simultaneous saccharification and fermentation (SSF) of oil palm empty fruit bunch (EFB) kraft pulp by cellulase and Saccharomyces cerevisiae MK 1 were studied. Substrate concentration was varied from 10 to 20%. Cellulase was added at 4 g-1 substrate, while the yeast inoculum was 10% (w v-1). The SSF process was carried out at 37°C, pH 4.5, 100 rpm for 76 hours. Ethanol production were obtained after 24 hours, however, ethanol concentration was decreased after 60 hours of fermentation. The highest ethanol concentration was obtained from samples with substrate concentration of 15% (w v-1). A much higher ethanol concentration was produced when that particular substrate was supplemented with 2% of sugar.